2023
DOI: 10.3390/polym15040907
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and In Vitro Evaluation of Chitosan-g-Oligolactide Based Films and Macroporous Hydrogels for Tissue Engineering

Abstract: In the current study, novel matrices based on chitosan-g-oligo (L,L-/L,D-lactide) copolymers were fabricated. In particular, 2D films were prepared by solvent casting, while 3D macroporous hydrogels were obtained by lyophilization of copolymer solutions. Copolymers of chitosan (Chit) with semi-crystalline oligo (L,L-lactide) (Chit-LL) or amorphous oligo (L,D-lactide) (Chit-LD) were obtained by solid-state mechanochemical synthesis. The structure of the hydrogels was found to be a system of interconnected macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…In addition, swelling properties could affect degradation rate. Earlier, the degradation rate was shown to increase along with swelling degree enhancement [ 39 , 40 ]. Moreover, the mechanical properties of wet hydrogels were found to be significantly reduced [ 9 , 22 ], which could negatively affect cell adhesion, morphology and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, swelling properties could affect degradation rate. Earlier, the degradation rate was shown to increase along with swelling degree enhancement [ 39 , 40 ]. Moreover, the mechanical properties of wet hydrogels were found to be significantly reduced [ 9 , 22 ], which could negatively affect cell adhesion, morphology and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer structure expands as the hydrogel hydrates, increasing the pore size. Tolstova et al [44] reported similar mean pore size (150 ± 5 µm) for chitosan hydrogels produced by the freeze-drying and thermal crosslinking process (150 • C for 5 h). The authors used fluorescamine as amino-specific staining to observe the macrostructure of chitosan hydrogels.…”
Section: Microstructure By Confocal Microscopymentioning
confidence: 85%
“…For example, Azueta-Aguayo et al [25] described that pore sizes of about 100 µm are suitable for cell proliferation. In addition, the interconnected porous structures, and the high degree of porosity of the scaffolds can provide good nutrient and oxygen transfer, resulting in improved cell migration and ECM production inside the scaffolds [8,44].…”
Section: Microstructure By Confocal Microscopymentioning
confidence: 99%
“…Hydrogels can be categorized based on their pore size, which determines their permeability and ability to accommodate different-sized molecules or cells. This classification includes macroporous hydrogels [144], mesoporous hydrogels [145], and microporous hydrogels [146]. Hydrogels can be classified based on their physical appearance, such as transparent hydrogels [147], opaque hydrogels, or hydrogel films [45].…”
Section: Artificial Cartilagementioning
confidence: 99%